Magnetic particles in motion: magneto-motive imaging and sensing - Kubelick, Kelsey P.; Mehrmohammadi, Mohammad (Theranostics, 2022)
Superparamagnetic nanoparticles have become an important tool in biomedicine. Their biocompatibility, controllable small size, and magnetic properties allow manipulation with an external magnetic field for a variety of diagnostic and therapeutic applications. Recently, the magnetically-induced motion of superparamagnetic nanoparticles has been investigated as a new source of imaging contrast. In magneto-motive imaging, an external, time-varying magnetic field is applied to move a magnetically labeled subject, such as labeled cells or tissue. Several major imaging modalities such as ultrasound, photoacoustic imaging, optical coherence tomography, and laser speckle tracking can utilize magneto-motive contrast to monitor biological events at smaller scales with enhanced contrast and sensitivity. In this review article, an overview of magneto-motive imaging techniques is presented, including synthesis of superparamagnetic nanoparticles, fundamental principles of magneto-motive force and its utility to excite labeled tissue within a viscoelastic medium, current capabilities of magneto-motive imaging modalities, and a discussion of the challenges and future outlook in the magneto-motive imaging domain.